ELECTRICAL RESESTIVITY INVESTIGATION FOR GROUNDWATER OF THREE VILLAGES IN SUMEL DISTRICT-DUHOK CITY NORTH OF IRAQ - Zainab M. Shanshal (Tikrit Journal of Pure Science, 2018)
A geophysical Electrical survey was conducted by applying Electrical Resistivity Sounding (VES) in three different villages located in Sumel district, which are belongs to Duhok city within the southern limb of Baikher anticline  in northern of Iraq, in order to investigate the groundwater to dig wells for drinking and agriculture purposes which didn’t have available wells in villages. The survey involved sixteen vertical electrical sounding (VES) points along three profiles using a schlumberger array to investigate the subsurface aquifer of the area as well as evaluation of the groundwater aquifer characteristics in the regions. The depth of the penetration in the current study reached more than (150) m. The electric resistivity values ranged between (10-70) Ω.m. It has been recognize three geoelectrical zones at different depths in the three study areas. The first zone have electric resistivity values ranged between (20-50) Ω.m, which represented the recent deposits with the presence clay in some areas. The second zone have electric resistivity values ranged between (11-17) Ω.m, which represented a layer of sandstone of multiple sizes and saturated with groundwater, the third zone have electric resistivity values ranged between (22-55) Ω.m , which represented layers of claystone with the presence of silt in some depths. it has been observe the existence of a semi-confined groundwater aquifer due to the presence of permeable layers of sandstone and in most of the regions it is surrounded by impermeable layers of claystone rocks, and it has been determined the level of groundwater in the study areas. According to this information it has been dig the wells in those areas and found the water in depths very close from that it is reached in the vertical electrical sounding.